2006
DOI: 10.1007/s10571-006-9039-7
|View full text |Cite
|
Sign up to set email alerts
|

The Number of Proliferating Cells in the Rostral Migratory Stream of Rat During the First Postnatal Month

Abstract: The objective of this study was to analyze neurogenesis in the rat rostral migratory stream (RMS) during the first postnatal month.1. During the early postnatal development some morphological changes, concerning the RMS thickness, shape, and the olfactory ventricle persistence at P0 were observed. 2. Bromodeoxyuridine (BrdU) immunohistochemistry and subsequent quantification of proliferating cells showed significant age-dependent changes. The highest number of proliferating cells was found at P3 and significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 20 publications
2
22
0
Order By: Relevance
“…Previously we have demonstrated that there are physiological changes in mitotic activity in the RMS during the first postnatal month. The lowest number of proliferating cells has been noted at day P7 [9]. In maternally deprived rats of the same age, the low density of dividing cells was even more striking (Figure 2).…”
Section: Cell Proliferationmentioning
confidence: 81%
See 1 more Smart Citation
“…Previously we have demonstrated that there are physiological changes in mitotic activity in the RMS during the first postnatal month. The lowest number of proliferating cells has been noted at day P7 [9]. In maternally deprived rats of the same age, the low density of dividing cells was even more striking (Figure 2).…”
Section: Cell Proliferationmentioning
confidence: 81%
“…The early postnatal RMS is U-shaped because the elbow between the vertical and horizontal arms is not as sharp compared to later postnatal stages. The typical "L"-shaped column, characteristic of the adult rat RMS, develops in two week-old rats [9].…”
Section: Introductionmentioning
confidence: 99%
“…The proliferation activity of ependymal cells was assessed by the most commonly used markers of cell division: BrdU and Ki-67, respectively. BrdU immunohistochemistry has regularly been applied for estimating proliferating cells number in the main neurogenic region of the brain under physiological conditions [24] and in experimental interventions [25,26]. The more recently introduced marker, Ki-67 is also commonly used for detection of proliferation in the brain [27] and the spinal cord [16].…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with findings of Uberti et al (2001), who detected a biphasic response to irradiation in dentate gyrus in mice, characterized by an early inhibition and delayed stimulation of cell proliferation. Later effects of ionizing radiation may involve the population of quiescent stem or precursor cells that appear to be responsible for repopulating of damaged SVZ Martončíková et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Under physiological conditions, this process is closely associated with simultaneous reduction in the number of stem or precursor cells via apoptosis (Brunjes & Armstrong 1996;Thomaidou et al 1997). The effects of ionizing radiation on the rat brain have been studied primarily in prenatal and neonatal animals (Shinohara et al 1997;Amano et al 2002) as well as in adults (Peissner et al 1999;Martončíková et al 2006). Acute low dose irradiation (0.5 Gy) has effect on various metabolic pathways that do not appear to be directly involved in cell death (Silasi et al 2004).…”
Section: Introductionmentioning
confidence: 99%